T cell metabolism in kidney immune homeostasis - Liu, Zikang; Dai, Binbin; Bao, Jiwen; Pan, Yangbin (Frontiers in Immunology, 2024)
Kidney immune homeostasis is intricately linked to T cells. Inappropriate differentiation, activation, and effector functions of T cells lead to a spectrum of kidney disease. While executing immune functions, T cells undergo a series of metabolic rewiring to meet the rapid energy demand. The key enzymes and metabolites involved in T cell metabolism metabolically and epigenetically modulate T cells' differentiation, activation, and effector functions, thereby being capable of modulating kidney immune homeostasis. In this review, we first summarize the latest advancements in T cell immunometabolism. Second, we outline the alterations in the renal microenvironment under certain kidney disease conditions. Ultimately, we highlight the metabolic modulation of T cells within kidney immune homeostasis, which may shed light on new strategies for treating kidney disease.